Resource Needs Assessment for Developing the Non- Textbook ‘Persahabatan Besi dan Magnet’ Based on the SDGs Framework in Junior High Schools - Wulan, Sinta Srie; Rubini, Bibin; Ardianto, Didit (Journal of Innovative Science Education, 2025)
This study assessed the resource needs for developing a non-textbook titled "Persahabatan Besi dan Magnet" or "The Friendship of Iron and Magnets", designed to enhance conceptual understanding of magnetism among junior high school students. Using a quantitative descriptive method with survey techniques, data were collected from 31 science teachers and 28 ninth-grade students in Sukabumi City, West Java, Indonesia. The instrument consisted of closed and open-ended questionnaires focusing on the needs for learning media, preferred formats, and expectations for non-textbook content. The results show that teachers strongly prefer the inclusion of experimental activities (90.3%), visual illustrations (67.7%), contextual stories (64.5%), and links to video simulations (74.2%). Meanwhile, students indicated high interest in live experiments (75%), visual media, and science stories. In addition, teachers and students supported integrating environmental issues and technological innovation related to magnetism. These findings highlight the need for a contextual, visual, and narrative-based non-textbook aligned with the SDGs framework to support more meaningful and engaging science learning experiences in junior high schools